Using Metrics of Readiness Levels in Maturity Assessment of a Product or Technology for Application in JSCo “RZD” - A. V. Tulupov; I. P. Vasiliev; D. A. Ionov; E. V. Palatkina; A. N. Petrov; E. V. Chechetkin (Ekonomika Nauki)
The article is devoted to the methods for maturity assessment of an innovative product or technology for implementation at the enterprises of JSCo “RZD” and assessing the risks of not achieving the readiness level of innovative projects. The main principles, scope and effects of using methods are noted. The method was developed for JSCo “RZD” and based on the TPRL methodology for a complex assessment of the technological project readiness level with the improvement of the procedure, rules and the mathematical model of assessment in accordance with the management processes in the railway industry. Approbation of the proposed assessment methods was carried out on the examples of promising innovative proposals received by the “SingleWindow of Innovations of JSCo “RZD”.The methods can be used for: a) assessing the level of technology development in JSCo “RZD” and comparing the level of technological development of the Russian Railways holding with foreign analogue companies; b) making a management decision on financing a development project, or on purchasing an innovative product and (or) technology and introducing it into the production process of JSCo “RZD”; c) building and verifying a product (technology) development and implementation roadmaps; d) monitoring the implementation of a project for the development and implementation of a product (technology), etc.The application of the methods will improve the efficiency of innovation activities in JSCo “RZD”.